Choosing methods in mental health research : Mental health research from theory to practice / Mike Slade; Stefan Priebe - Slade, Mike
This book outlines how to choose the most helpful and appropriate mental health research method, not only to address a given research question, but also to maximise the potential impact of the research on shaping mental health care.